2021
DOI: 10.1080/21645515.2021.1969852
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Japanese encephalitis vaccines

Abstract: Japanese encephalitis (JE) is an endemic disease dominantly in the Asia-Pacific region with mortality rate varying between 3% and 30%. Long-term neuropsychiatric sequelae developed in 30-50% of the survivors. There is no available antiviral therapy for JE. JE vaccines play a major role in preventing this devastating disease. The incidence of JE declined over years and the age distribution shifted toward adults in countries where JE immunization program exists. Mouse brain-JE vaccine is currently replaced by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…All of these vaccines were based on genotype III of JEV but showed cross-reactivity against genotypes I-IV [ 151 ]. The formulation of all four types of vaccines (Table 1 ) have been reviewed by Turtle and Solomon [ 16 ], and their immunogenicity and efficacy have been reviewed by Nagendra and Milind [ 152 ], Barzon and Palu [ 153 ], Kumar et al [ 154 ], Satchidanandam [ 155 ], Hu and Lee [ 156 ], and Kanamori et al [ 157 ]. In addition, Lee et al have reviewed the applicability and usage of inactivated Vero-cell-derived vaccines, live attenuated vaccines, and live recombinant vaccines [ 158 ].…”
Section: Recent Insights and Developments: Vaccines Therapeutics And ...mentioning
confidence: 99%
“…All of these vaccines were based on genotype III of JEV but showed cross-reactivity against genotypes I-IV [ 151 ]. The formulation of all four types of vaccines (Table 1 ) have been reviewed by Turtle and Solomon [ 16 ], and their immunogenicity and efficacy have been reviewed by Nagendra and Milind [ 152 ], Barzon and Palu [ 153 ], Kumar et al [ 154 ], Satchidanandam [ 155 ], Hu and Lee [ 156 ], and Kanamori et al [ 157 ]. In addition, Lee et al have reviewed the applicability and usage of inactivated Vero-cell-derived vaccines, live attenuated vaccines, and live recombinant vaccines [ 158 ].…”
Section: Recent Insights and Developments: Vaccines Therapeutics And ...mentioning
confidence: 99%
“…Compared with inactivated vaccines, live-attenuated vaccines based on SA14-14-2 have better immunogenicity and a more convenient immunization program. However, the incidence in adults has increased in recent years, suggesting that a live-attenuated vaccine may not provide long-term effective protection [3][4][5]. In addition, the populations in some Asian countries are worried about the safety of live vaccines and choose inactivated vaccines which are relatively less effective [6] Other types of JEV vaccines, such as recombinant protein subunit vaccines and DNA vaccines, have been previously reported to show effective protection in mice [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The former ‘inactivated mouse‐brain derived’ vaccine for JE is also having some set of problems like poor long‐term immunity and allergic reactions. Later it was replaced by Vero cell‐derived vaccines, live‐attenuated vaccine using SA14‐14‐2 strain, and live chimaeric JE vaccine, which have been shown to have favourable efficacy and safety 8 . The complexity of diagnosing and detecting the disease at the first phase marks it under the group of severe infections due to its lower viral load 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Later it was replaced by Vero cellderived vaccines, live-attenuated vaccine using SA14-14-2 strain, and live chimaeric JE vaccine, which have been shown to have favourable efficacy and safety. 8 The complexity of diagnosing and detecting the disease at the first phase marks it under the group of severe infections due to its lower viral load. 9 It was also suggested that there was no certain list of biomarkers which can help in the identification of disease at pilot stages, and it claims that the infection is a progressive blind model during its initial stages.…”
mentioning
confidence: 99%